2023
DOI: 10.5194/acp-23-15413-2023
|View full text |Cite
|
Sign up to set email alerts
|

Opinion: Tropical cirrus – from micro-scale processes to climate-scale impacts

Blaž Gasparini,
Sylvia C. Sullivan,
Adam B. Sokol
et al.

Abstract: Abstract. Tropical cirrus clouds, i.e., any type of ice cloud with tops above 400 hPa, play a critical role in the climate system and are a major source of uncertainty in our understanding of global warming. Tropical cirrus clouds involve processes spanning a wide range of spatial and temporal scales, from ice microphysics on cloud scales to mesoscale convective organization and planetary wave dynamics. This complexity makes tropical cirrus clouds notoriously difficult to model and has left many important ques… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 332 publications
(350 reference statements)
1
2
0
Order By: Relevance
“…More work is needed to better understand the processes governing high-cloud optical depth in nature (including those that determine cloud phase, total water content, particle sizes, and other cloud microphysical properties) and its changes in response to interannual temperature variations. This echoes recent studies arguing for the importance of examining high-cloud optical depth feedbacks (Gasparini et al, 2023;Li et al, 2019;McKim et al, 2024;Zelinka et al, 2022). The consistent underestimation in high cloud feedbacks motivates further work to analyze how high clouds respond to their cloud controlling factors.…”
Section: Discussionsupporting
confidence: 66%
“…More work is needed to better understand the processes governing high-cloud optical depth in nature (including those that determine cloud phase, total water content, particle sizes, and other cloud microphysical properties) and its changes in response to interannual temperature variations. This echoes recent studies arguing for the importance of examining high-cloud optical depth feedbacks (Gasparini et al, 2023;Li et al, 2019;McKim et al, 2024;Zelinka et al, 2022). The consistent underestimation in high cloud feedbacks motivates further work to analyze how high clouds respond to their cloud controlling factors.…”
Section: Discussionsupporting
confidence: 66%
“…This is particularly noticeable in the thin cirrus samples with COD ≤ 0.1 (Figure 2f). This phenomenon is associated with the abundance of tropical tropopause layer (TTL) cirrus clouds generated by circulation and gravity waves in the tropics (Gasparini et al, 2023;Sassen et al, 2009).…”
Section: Geophysical Research Lettersmentioning
confidence: 99%
“…In higher cirrus clouds, particularly near the tropopause, crystals tend to become nearly quasi-spherical (droxtals), which is attributed to the sublimation and the decrease in atmospheric water vapor content, leading to slower vapor deposition rates (Woods et al, 2018). Following the growth of ice crystals through vapor deposition, variations in falling or rising speed result in collisions and adhesion, leading to the formation of aggregates (Gasparini et al, 2023;Sölch & Kärcher, 2011). The newly introduced Voronoi model has demonstrated greater suitability for retrieving microphysical properties and conducting • Hollow characteristic cirrus clouds radiative assessments of ice clouds compared to the plates and columns aggregation models employed in the past (Letu et al, 2016;Li et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, regional studies in the Pacific have revealed complex patterns of CRE of upper-level clouds, with positive CREs observed for single-layered thin clouds colder than 260 K, peaking for very cold clouds which has their optical thickness around 1, and decreasing with increased thickness 9 . In summary, despite numerous studies investigating the radiative effect of TUCs, findings have shown variability due to differences in the target region, observational instruments, and the methodologies used to define TUCs 10 .…”
Section: Introductionmentioning
confidence: 99%